The Efficiency and Productivity of Indian Pharmaceutical Companies A Firm-Level Analysis - Mohammad, Aas (Cambridge Scholars Publisher, 2019)
This book evaluates the performance of the Indian pharmaceutical industry, which plays an important role in economic development. It highlights the role the government has had in facilitating the growth of the industry from non-existence, before the 1970s, to being one of the largest pharmaceutical industries in the world today. The text employs various useful techniques to provide an understanding of productivity and efficiency, such as data envelopment analysis, stochastic frontier analysis, the Malmquist Productivity Index and the Hicks-Moorsteen Productivity Index. The book will be useful to health administrators, students of public policy, and health economists with an interest in the pharmaceutical sector